Follicular flushing during oocyte retrieval in assisted reproductive techniques. - Supreeya Wongtra-Ngan (2018)
BACKGROUND: Ultrasound guided transvaginal aspiration of oocytes has replaced other methods of oocyte retrieval for in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI). However, there is controversy over whether flushing yields a larger number of oocytes and a higher potential for pregnancy than aspiration only. OBJECTIVES: To determine whether follicular aspiration and flushing increases live birth or ongoing pregnancy rates and the number of oocytes over aspiration alone in women undergoing IVF and ICSI. SEARCH STRATEGY: We searched the Menstrual Disorders and Subfertility Group Specialised Register of controlled trials, MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO and the citation lists of relevant publications (to April 2010). SELECTION CRITERIA: Randomised controlled trials that compared follicular aspiration and flushing with aspiration alone were included. Trials were excluded if the flushing method comparison was confounded by comparisons of other methods. DATA COLLECTION AND ANALYSIS: Eligible studies were assessed for methodological quality. For dichotomous data, odds ratios (OR) and 95% confidence intervals (CI) were calculated. For continuous data, mean differences were reported. The heterogeneity of the studies was examined by using statistical tests of homogeneity and the I(2) statistic. MAIN RESULTS: No studies reported on the primary outcome of live birth. There was no evidence (3 studies, 164 patients) to suggest an association between follicular aspiration and flushing and ongoing or clinical pregnancy per woman randomised (OR 1.17, 95% CI 0.57 to 2.38). There was no evidence of a difference in adverse events reported between follicular aspiration and flushing and aspiration only. There was no evidence of significant differences in increased oocyte yield per woman randomised (1 study, 44 patients). Without flushing the operative time was significantly shorter, by 3 to 15 minutes (3 studies, P < 0.001) and the dose of pethidine required was significantly less (50 mg versus 100 mg, P < 0.00001). AUTHORS' CONCLUSIONS: There is no evidence that follicular aspiration and flushing is associated with improved clinical or ongoing pregnancy rates, nor an increase in oocyte yield. The operative time is significantly longer and more opiate analgesia is required for pain relief during oocyte retrieval. There is a lack of evidence regarding the effect of follicular aspiration and flushing on live birth rates in the identified data.